Systematic review the criteria for Building Performance Evaluation (BPE) - Sotsek, Nicolle Christine; Leitner, Drielle Sanchez; Lacerda Santos, Adriana de Paula (Revista ALCONPAT, 2018)
The objective of this article is to provide, through a systematic review of the literature focused on quality control of buildings, a consistent database to present the criteria most used by the Building Performance Evaluation (BPE). Through this review, 782 articles were identified, of which 15 were selected considering the subject's adherence to the research and publication period. The main information about the articles, their authors and journals was discussed. The performance criteria compiled by the analyzed articles used as basis: literature, questionnaires and interviews with users and professionals of the area, consultation with specialists in the segment and technical visits to buildings. With these identified criteria it was possible to define 9 dimensions of analysis that are discussed and presented in this document.